Effect of polymerization sources on the marginal sealing of single-increment resin restorations - Claudia Castillo Guillén; Marco Antonio Sánchez Tito (Editorial Ciencias Médicas, 2022)
Introduction: Single-increment resins allow a photoactivation of 4 to 5 mm deep, reducing the clinical time of application. However, factors such as shrinkage that may affect the marginal sealing of the restoration should be considered. Objective: Evaluate the effect of three polymerization sources on the marginal sealing of Class II restorations, carried out with three single-increment resin systems. Methods: An in vitro experimental study was conducted. The calculation of the number of study units was carried out with the EPIDAT software, for which the means of two previous studies were taken. Nine subgroups were made according to the restoration material and the polymerization source. Two Class II restorations were made on each tooth, which were carried out according to the manufacturer's instructions. The teeth were subjected to passive immersion in 1% methylene blue for 24h. The teeth were sectioned mesiodistally. Photographs were taken with a Canon camera and a 100mm macro lens. Marginal filtration was measured on a scale of 0 to 4. Data were analyzed with Kruskal-Wallis tests for group comparison. A significance level adjusted to 5% was established. Results: The resin with the lowest filtration level was Filtek Bulkfill, with 53.3% corresponding to scale 0, while the resin with the highest filtration was Tetric N-Ceram Bulk Fill with 76.7% (scale 4), similar to Sonicfill (70.0%). Conclusions: The different polymerization sources did not influence the level of filtration between the three single-increment resin systems. Filtek Bulkfill presented a better marginal seal when compared to SonicFill and Tetric N-Ceram Bulk Fill.